2009
DOI: 10.1063/1.3157202
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of p-type CoSb3 nanocomposites with dispersed CoSb3 nanoparticles

Abstract: Articles you may be interested inTheoretical and experimental approach on dielectric properties of ZnO nanoparticles and polyurethane/ZnO nanocomposites J. Appl. Phys. 112, 054106 (2012); 10.1063/1.4749414 Improved thermoelectric performances in nano-Co0.97Pd0.03Sb3 AIP Conf.CoSb 3 nanocomposites with different contents of CoSb 3 nanoparticles were prepared by mixing nanosized CoSb 3 particles obtained via polyol method and micron-sized particles obtained via solid state reaction. X-ray diffractometer and fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…At 300 K the thermal conductivity was reduced by 40% for the ball-milled sample without Ag additions. This is in line with results on other materials, where reductions of 50% in BiSbTe 10 and 60% in CoSb 3 16 have been reported. Adding Ag particles to the ballmilling of ZnSb did not yield any further reductions in the thermal conductivity in the present case.…”
Section: Resultssupporting
confidence: 94%
“…At 300 K the thermal conductivity was reduced by 40% for the ball-milled sample without Ag additions. This is in line with results on other materials, where reductions of 50% in BiSbTe 10 and 60% in CoSb 3 16 have been reported. Adding Ag particles to the ballmilling of ZnSb did not yield any further reductions in the thermal conductivity in the present case.…”
Section: Resultssupporting
confidence: 94%
“…4 In fact, in our earlier work, we successfully synthesized CoSb 3 nanostructures via a polyol method and showed that reduction in thermal conductivity was achieved. 5,6 Hence, in this work, our motivation is to enhance TE performance further by improving the electrical properties of nanostructured CoSb 3 through adjusting the Co and Sb composition in the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Skutterudites have an effective TE operational range from 650K to 950 K. Among the different types of skutterudites compounds, CoSb 3 based members have attracted by far the greatest interest because of constituents' abundant availability and less cost [7]. Iron substituted CoSb 3 , FexCo 1-x Sb 3 , have been reported to display good performance as a p-type TE material, in terms of its TE figure of merit (ZT), and abundance of the constituent elements [8][9][10][11][12][13][14]. The ZT can be improved via introduction of dopants, nanoengineering and in case of skutterudites, introducing rare earth elements in the crystal cages to reduce the thermal conductivity [1,[4][5][6] due to rattling of the fillers.…”
Section: Introductionmentioning
confidence: 99%